Preventing intolerant understandings, attitudes, and behaviors among generation Z muslims in public and Islamic schools - Purba, Mariati; Hadiana, Deni; Darraz, Muhammad Abdullah; Ariantoni; Hendrawati, Sri; Helmy, Muhammad Irfan (Indonesian Journal of Islam and Muslim Societies, 2024)
This research aims to explore school efforts to enhance resilience against intolerance through school policies. The study builds upon a survey conducted by previous researchers, which revealed that intolerant thoughts, attitudes, and behaviors have influenced Generation Z Muslim students in high schools. This research employs a qualitative method by conducting an in-depth and comprehensive analysis of the phenomena and the meaning of events, social dynamics, attitudes, beliefs, and perceptions of individuals or groups closely related to intolerance in high schools. The phenomena are examined through interviews, observations, and focus group discussions (FGD). The research findings conclude that schools have implemented various measures to enhance the resilience of the school community members through both internal and external policies. These include school policies and vision, curriculum quality and teaching, leadership and management, culture, student activities, and collaboration with external parties, including the facilitation of extracurricular activities. The research provides recommendations for more comprehensive efforts by developing a model of school policy insertion, both internal and external, that emphasizes tolerance values and prevents violence in schools.